Effect of mexidol on physical and mental performance under stressogenic conditions in experiment - I. G. Kapitsa; E. A. Ivanova; T. A. Voronina (LLC "Publisher OKI", 2019)
The effect of Mexidol on physical performance of mice under the extreme conditions of the weight-loaded forced swim test and on the mental performance of rats under the conditions of a neurosis-like state caused by a functional disturbance of a defensive instrumental conditioned active avoidance reflex was studied. A single dose (50 and 100 mg/kg) or a subchronic regimen (100 mg/kg) of Mexidol administered intrapertoneally enhances the physical performance of mice similarly to mildronate (100 mg/kg). Mexidol improves the rate of operant conditioning, the preservation of the memory trace and its restoration after single or multiple instances of disruption of the conditioned active avoidance reflex, and its effect does not differ from the effect of the comparison drug piracetam (300 mg/kg).